2022
DOI: 10.1001/jamapediatrics.2021.5683
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal SARS-CoV-2 Immunoglobulin G Antibody Levels at Delivery After Receipt of the BNT162b2 Messenger RNA COVID-19 Vaccine During the Second Trimester of Pregnancy

Abstract: IMPORTANCE BNT162b2 messenger RNA (mRNA) COVID-19 vaccination in the third trimester was found to be associated with a strong maternal humoral IgG response that crossed the placenta and approached maternal titers in the newborn.OBJECTIVE To evaluate maternal and neonatal SARS-CoV-2 immunoglobulin G (IgG) antibody levels at birth after mRNA COVID-19 vaccination during the second trimester of pregnancy. DESIGN, SETTING, AND PARTICIPANTSThis prospective cohort study, conducted at a single medical center in Haifa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 27 publications
8
67
3
2
Order By: Relevance
“…In addition, studies have found that Pfizer vaccine can induce effective maternal to neonatal transfer of IgG [29,43,62]. The longer the time interval from vaccination to delivery, the higher the maternal and neonatal antibody levels and the cord-to-maternal ratio [63,64]. After the receipt of the second vaccine dose, the maternal and neonatal antibody levels change by −10.9% and −11.7% per week [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have found that Pfizer vaccine can induce effective maternal to neonatal transfer of IgG [29,43,62]. The longer the time interval from vaccination to delivery, the higher the maternal and neonatal antibody levels and the cord-to-maternal ratio [63,64]. After the receipt of the second vaccine dose, the maternal and neonatal antibody levels change by −10.9% and −11.7% per week [63].…”
Section: Discussionmentioning
confidence: 99%
“…The longer the time interval from vaccination to delivery, the higher the maternal and neonatal antibody levels and the cord-to-maternal ratio [63,64]. After the receipt of the second vaccine dose, the maternal and neonatal antibody levels change by −10.9% and −11.7% per week [63]. This suggests that maternal vaccination protects infants.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between antibody titers, feto-maternal characteristics, and the time interval from vaccination to delivery were analyzed after the completion of data gathering. Maternal and neonatal IgG antibodies from the current study were compared to antibody levels measured after second trimester 2-dose vaccination in a previous study published by our group [14] . In addition, transplacental SARS-CoV-2 IgG antibody transfer ratios were calculated by dividing neonatal (umbilical cord blood) IgG levels, by the IgG antibody levels in paired maternal blood.…”
Section: Methodsmentioning
confidence: 99%
“…Circulating anti-S1 RBD antibody is also only one measure of immune protection and does not account for aspects of immunologic memory. Although we did not specifically measure neutralizing antibody, anti-S IgG correlates closely with neutralizing activity patterns 16,38 .…”
Section: Discussionmentioning
confidence: 94%
“…Yang et al found that early third trimester vaccination led to highest anti-spike IgG levels 31 . Kugelman et al reported that second trimester mRNA vaccination led to protective IgG levels at delivery 38 , while Rottenstreich et al reported that IgG levels were lowest after first trimester and highest after 3 rd trimester vaccination 32 . Our data, although limited to second and third trimester vaccination, shows clear evidence that vaccination results in superior antibody levels and transfer ratios compared to infection, and that this difference is pronounced with longer latency.…”
Section: Discussionmentioning
confidence: 99%